Crossing the blood-brain barrier: a review on drug delivery strategies using colloidal carrier systems - Mahringer, Anne; Puris, Elena; Fricker, Gert (Neurochemistry international, 2021)
The blood-brain barrier represents the major challenge for delivering drugs to the central nervous system (CNS). It separates the blood circulation from the brain tissue, thereby protecting the CNS and maintaining its ion homeostasis. Unfortunately, most drugs are not able to cross this barrier in vivo despite promising in vitro results. One approach to solve this problem is the delivery of drugs via surface modified nanocarrier systems. This review will give an overview on currently tested systems, mainly liposomes and solid nanoparticles and inform about new developments.
Gesehen am 20.07.2021